ANALISIS KONFLIK BATIN YANG DIALAMI TOKOH UTAMA PADA NOVEL 3726 MDPL KARYA NURWINA SARI - Nilam Suryaning Pungkasari; Mustofa; Hendrik Furqon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of inner conflict experienced by the main character in the novel 3726 MDPL by Nurwina Sari using a literary psychology approach based on Abraham Maslow's hierarchy of needs theory. This research employed a qualitative descriptive method. The data source was the novel 3726 MDPL, while the data consisted of words, phrases, sentences, dialogues, and narratives indicating the main character's inner conflicts. Data were collected through library research using reading and note-taking techniques. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that the main character, Rangga, experienced various forms of inner conflict related to the fulfillment of Maslow's hierarchy of needs. These conflicts include safety needs reflected in trauma caused by parental divorce, love and belonging needs reflected in loneliness, expectations of love, disappointment, and deep sadness, esteem needs reflected in feelings of failure, lack of appreciation, and self-disappointment, and self-actualization needs reflected in inner struggles regarding future career decisions. Rangga's inner conflicts emerged due to the imbalance between expectations and reality in his life. This study demonstrates that Abraham Maslow's theory of needs can be effectively applied to reveal the psychological dynamics of literary characters.